Aspects of Morphological Miracles in Quranic Readings through Interpretation (Verses from the Holy Quran as a model) - حميدات, الجمعي (Milev Journal of Research and Studies, 2023)
Since the time of the Messenger of God, blessing and peace be upon him, Muslims have shown a great interest in the Holy Qur'an in knowledge and learning, both in the Qur'an and recitation - and despite their different orientations - in particular since the Holy Qur'an represents the constitution of their life and its divine approach, which requires a work of attention and a work of study of the aspects of clarification and miraculous in it. This interest has sparked numerous studies that have looked at its linguistic miracle. In general and his morphological miracle on the other hand, especially when his readings were numerous and the vocal error widespread among his readers... Apure morphological studies based on the observation of the variation of readings and its impact on the meaning in the form of words (nouns and verbs), and morphological formulas that include verbs in terms of conjugation with pronouns, and in nouns in terms of meaning, masculine and feminine, and in terms of number, singular and plural…